Analysis of Students’ Ability in Reading Aloud at Grade VIII-A of UPTD SMP Negeri 1 Gunungsitoli - Erika Zalukhu; Riswan Zega; Trisman Harefa; Kristof Martin Efori Telaumbanua (Jurnal Pendidikan dan Sastra Inggris, 2025)
Reading aloud is an important basic skill in English language learning. However, students in class VIII-A UPTD SMP Negeri 1 Gunungsitoli are facing difficulties in reading aloud, such as incorrect pronunciation, monotonous intonation, low voice volume, and lack of expression. This study aims to analyze students' ability to read aloud and the factors that influence it. This study used a descriptive qualitative approach with 32 students as subjects. Data were collected through observation, reading aloud tests, interviews, and documentation. The assessment was based on four aspects: pronunciation and clarity, fluency, volume, and intonation with expression. Data analysis used the Miles and Huberman model. The results showed that most students were in the low and very low categories, and there were no students who reached the excellent category. Errors most often occurred in pronunciation and intonation, which indicates limited vocabulary mastery and weak phonological awareness. Internal factors such as lack of confidence, low motivation, and limited vocabulary were found to hinder performance. External factors, including an unsupportive learning environment and minimal practice opportunities, also contributed to students’ difficulties. In conclusion, students' ability to read aloud still needs significant improvement through regular practice, vocabulary enrichment, and teacher support in creating a conducive and engaging classroom atmosphere. This research is expected to provide input for teachers in designing reading activities that emphasize pronunciation, fluency, and expression to help students build confidence and improve overall English proficiency.